Stimulation of the farnesoid X receptor promotes M2 macrophage polarization - Jaroonwitchawan, Thiranut; Arimochi, Hideki; Sasaki, Yuki; Ishifune, Chieko; Kondo, Hiroyuki; Otsuka, Kunihiro; Tsukumo, Shin-ichi; Yasutomo, Koji (Frontiers in Immunology, 2023)
FXR is a key molecule that modulates anti-inflammatory activity in the intestinal-liver axis. Although FXR has pleiotropic functions including regulation of liver inflammation and activation of macrophages, it remains unclear whether it is involved in macrophage polarization. In this paper we demonstrated that stimulation of macrophages derived from the bone marrow using an FXR agonist activated polarization toward M2 but not M1 macrophages. The treatment of mice with chitin skewed macrophage polarization towards M2 macrophages, while co-treatment with an FXR agonist further promoted the polarization toward M2 macrophages in vivo. This skewed polarization towards M2 macrophages by an FXR agonist was accompanied by increased expression of signaling molecules related to the retinoic acid receptor. Inhibition of the retinoic acid receptor suppressed FXR agonist-mediated M2 macrophage polarization, indicating that this polarization was, at least, partly dependent on the retinoic acid receptor pathway. These data demonstrate that FXR has a role in polarization toward M2 macrophages and suggest a possible therapeutic potential of FXR agonists in M2 macrophage-related conditions.